Integrasi Keterampilan Berpikir Kritis dalam Buku Teks Bahasa Indonesia Kurikulum 2013 Berperspektif HOTS - Duwi Saputro; Atiqa Sabardila; Harun Joko Prayitno; Markhamah Markhamah (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This study aims to describe thinking skills in Indonesian Language Learning Textbook class X Curriculum 2013. The thinking skills in this study are oriented towards revising Bloom's learning taxonomy which divides thinking skills into two domains, namely Lower Order Thinking Skills (LOTS) and Higher Order Thinking Skills (HOTS). The data in this study are in the form of text learning objectives written in Indonesian textbooks. The data is sourced from two revised editions of Indonesian textbooks, namely the 2014 revision and the 2017 revision. The data analysis method used in this study is referential matching and mapping of educational objectives based on the revised Bloom's taxonomy. The integration of thinking skills in Indonesian textbooks is manifested in the cognitive and knowledge dimensions. The cognitive dimension is dominated by the level of creation (C6) accumulated from two revised books. The knowledge dimension is dominated by conceptual knowledge. Based on this dominance, it can be concluded that the primary outcome of learning Indonesian is text creation. The text created is constructed from the concepts of text knowledge obtained in the learning process.